Doctor Who Club of Australia (Sydney : Doctor Who Club of Australia, 2007)
The Doctor Who Club of Australia is an organisation for fans of the BBC television programme Doctor Who. Site contains club and promotional information.
Title from title page (viewed on 20th April 2009)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.doctorwhoaustralia.org
Selected for archiving
Keywords: Doctor Who (Television program : 2005- ); Science fiction fans -- Societies, etc; Science fiction -- Societies, etc